The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.29062/mahardika.v18i2.159
|View full text |Cite
|
Sign up to set email alerts
|

HAMBATAN €“ HAMBATAN DALAM UPAYA PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM) DENGAN MENGGUNAKAN TEKNOLOGI INFORMASI ( E-Commerce ) UNTUK MENINGKATKAN PENJUALAN BIBIT IKAN DI DESA PLOSOBUDEN KEC.DEKET KAB. LAMONGAN

Abstract: This research focuses the problems on how the business barrier analysis that uses e-commerce for sellers of fish seedlings in the village Buden. The theory used in this study is the Uses and Gratifications theory. Methods of research using qualitative research methods. For retrieval information and data set set 5 informant. The data collection techniques used in this research are structured interviews directly. The results of the study found that fundamental issues were delays in shipping products from sellers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…While the programs made by the three business communities were almost the same, one area where the assistants did not have social enthusiasm caused the activity to not run well, this area even had very many problems in terms of working together and approaching members. (Kusbandono & Rosyad, 2019) in his research found that the community has a very good role in the progress of community members. MSME members find it very helpful, especially in terms of the social dimension.…”
Section: Social Dimensionmentioning
confidence: 99%
“…While the programs made by the three business communities were almost the same, one area where the assistants did not have social enthusiasm caused the activity to not run well, this area even had very many problems in terms of working together and approaching members. (Kusbandono & Rosyad, 2019) in his research found that the community has a very good role in the progress of community members. MSME members find it very helpful, especially in terms of the social dimension.…”
Section: Social Dimensionmentioning
confidence: 99%
“…E-Commerce adalah kegiatan bisnis dengan tujuan mengambil keuntungan seperti penjualan, pembelian, pelayanan, informasi, dan perdagangan melalui perantara, yaitu melalui suatu jaringan komputer, terutama internet (Kusbandono & Rosyad, 2019).…”
Section: Hakikat E-commerceunclassified
“…Minat beli (Purchase Intention) merupakan faktor pendorong konsumen dalam melakukan pembelian produk (Bisma & Pramudita, 2019). Dengan kemampuan web atau internet yang bisa mengirimkan berbagai bentuk data seperti teks, grafik, gambar, suara, animasi, atau bahkan video, maka banyak kalangan bisnis yang memanfaatkan teknologi ini dengan membuat homepage untuk mempromosikan usahanya dan menarik minat konsumen (Kusbandono & Rosyad, 2019).…”
Section: Metode Penelitianunclassified